Les Rites de Passage: Ritual, Initiation, and the State in Works by Sigalit Landau and Anisa Ashkar. (2nd October 2018) - Sevilla-Sadeh, Nava
Abstract : Initiation or rites of passage in the ancient world constituted a highly meaningful experience and were intended to delineate the transition from childhood to adult status, with the sacred initiation meant to promise a merging with the divine. The argument at the heart of this research is that features of initiation and of the ancient Dionysian rituals can be found in works by Sigalit Landau (b. 1969) and Anisa Ashkar (b. 1979), as metaphors of contemporary initiation in relation to the establishment of the Israeli nation and the fate of the Arab inhabitants following the Nakba ("disaster" in Arabic), the exodus of the Palestinian and Arab dwellers after the establishment of the Israeli State in 1948. This article employs ancient texts and visual references as well as contemporary thought.